Kecenderungan Kajian Penelitian Jurnal Komunikasi Pada Penulis APJIKI Ditinjau dari Tujuh Tradisi Komunikasi (Profetik: Jurnal Komunikasi, 2019)
This research tries to reveal the trends and tendency of research studies conducted by the authors published in the journal of communication science incorporated in the Association of Journal Management Science Communication Indonesia (APJIKI). The publication demands made by the academic community of Higher Education give a considerable impact on the awareness of the lecturers the importance of conducting studies, research and writing scientific papers. Communication science study progressed along with the development of communication technology. The development of this communication study coloring the writing of scientific articles in the form of research and articles in communication journals, then this research synthesizes the results of writing in scientific journals in the field of communication science contained in APJIKI (Association of Publishers Journal of Communication Science) in Indonesia by using perspective approaches seven traditions in communication namely, semiotics, phenomenology, cybernetic, psychological social, socio-cultural, critical and rhetoric. This study is using a quantitative and qualitative approach, data obtained through the dissemination of an online questionnaire and interview. The results showed that the scope of research studies for communication journals incorporated in APJIKI year 2016 more inclined on the study Public Relations (PR). While the form of communication studies that ranked first in 2016 is a study on the form of mass communication.